The Role Of Market Performance Studies With A Strategic Orientation - Syam'un Syam'un; Roymon Panjaitan; Andry Mochamad Ramdan; Dhiraj Kelly Sawlani; Akmal Abdullah (Jurnal Manajemen Industri dan Logistik, 2022)
In Southeast Sulawesi, during the Corona Virus Disease Pandemic, this study sought to examine the impact of the strategic orientation dimension on the market performance of the culinary industry. The descriptive and quantitative methods used non-probability sampling and a purposive sample technique. During the COVID-19 pandemic, the population was made up of actors in the food industry who had managed to survive and run their companies for more than two years. Only 38 people responded to the survey's sample, which was small. This study used Smart-PLS  3.0's route analysis for data analysis. To help culinary business actors perform better in the market during the COVID-19 pandemic, the analysis of the strategic aspects that have an aggressive attitude and significantly affect market performance were presented.